THE SYMMETRY AS INTERDISCIPLINARY FACTOR THROUGH ITS APPLICATION AND HISTORY - Melo, Helena (European Scientific Journal, ESJ, 2014)
The symmetry is used by human race in his achievements since the most primitive times. The human being following the permanent evolution of life could not fail to put the symmetry in his works, once his own outward appearance of almost every being symmetric. In the archaeological remains and even in her earliest art manifestations we checked this fact. All over the world and for all the historical, the symmetry is an inseparable companion of human creation and everything that surrounds him.